Risk factors associated with antineoplastic chemotherapy-induced nausea and vomiting - Giovana Paula Rezende Simino; Ilka Afonso Reis; Francisco de Assis Acurcio; Eli Iola Gurgel Andrade; Natalia Maria Linhares Brazil; Mariângela Leal Cherchiglia (Universidade de São Paulo, 2020)
ABSTRACT OBJECTIVE: To estimate the incidence and to evaluate risk factors for antineoplastic nausea and vomiting with high and moderate emetogenic chemotherapy in adult patients in the first treatment cycle. METHODS: Prospective cohort study with follow-up of 269 adults during the first cycle of antineoplastic chemotherapy. The incidence of nausea and vomiting was evaluated in the acute phase (0-24 hours), in the late phase (24 hours-5th day) and in the total phase (0-5th day). RESULTS: In total, 152 patients underwent high emetogenic chemotherapy and 117 moderate emetogenic chemotherapy. The relative frequency of nausea was higher when compared with vomiting in the acute phase (p < 0.001) and in the late phase (p < 0.001). The risk factors identified were: age group ≤ 49 years (odds ratio = 0.47; 95%CI 0.23-0.95) and 50-64 years (odds ratio = 0.45; 95%CI 0.23-0.87), tobacco use (odds ratio = 0.35; 95%CI 0.14-0.88), and high emetogenic chemotherapy (odds ratio 0.55; 95%CI 0.31-0.95). CONCLUSION: The incidence of nausea was higher than that of vomiting, and adverse effects were more frequent in the late phase. The results suggest the risk factors for chemotherapy-induced nausea and vomiting are tobacco, age (young adults), and high emetogenic chemotherapy.